Wittgenstein's Clinical Philosophy (Nóema, 2017)
This article aims at drawing the principle boundaries of Wittgenstein's philosophy, by defining its operative area and strategic action. Firstly, it follows the changes in Wittgenstein's interpretation of language and of meaning. These changes will be used as a draft for sketching the equivalent reviews of goals, techniques and ways of doing philsophy that he proposed. Secondly, it analyses late Wittgenstein's philosophical practice, which will be interpreted as clinical.
Keywords: Wittgenstein; philosophy; language; meaning; science; action; description; clarification; therapy; clinical; pragmatism; Peirce